# 24 Generalized Binary Continuous Maps GB CMDefinition 241 Let XY? Essay

2.4. Generalized Binary Continuous Maps (G_B CM)

Definition 2.4.1: Let (X,Y,?) be G_B TS and (Z,T_G ) be G_T S. Then the map F:Z?X?Y is called generalized binary continuous (G_B CM) at z?Z if for any G_B OS (A,B)?(X,Y,?) with f(z)?(A,B) then there exists a T_G-open set G in (Z,T_G ) such that z?G and F(G)?(A,B). The map F is called G_B CM if it is G_B C at each z?Z.

Don't use plagiarized sources. Get Your Custom Essay on
24 Generalized Binary Continuous Maps GB CMDefinition 241 Let XY? Essay
GET AN ESSAY WRITTEN FOR YOU FROM AS LOW AS \$13/PAGE

Proposition 2.4.1: Let (X,Y,?) be G_B TS and (Z,T_G ) be G_T S. Let F:Z?X?Y be a mapping. Then F is called G_B CM if F^(-1) (A,B) is T_G-open in (Z,T_G) for every G_B OS (A, B) in (X,Y,?).

Proof: Let F be G_B CM and (A, B) be G_B OS in (X,Y,?).

If F^(-1) (A,B)=?. Then ? is T_G-open set. If F^(-1) (A,B)?? and let z?F^(-1) (A,B). Then F(z)?(A,B). Since F is G_B C at z, there exists a T_G-open set G in (Z,?_g ) such that z?G and F(G)?(A,B). Hence z?G?F^(-1) (A,B). Therefore F^(-1) (A,B) is T_G-open in (Z,T_G ).

Conversely to show that the mapping F:Z?X?Y is G_B C, let z?Z and (A, B) be a G_B OS in (X,Y,?) with F(z)?(A,B). Then z?F^(-1) (A,B), where F^(-1) (A,B) is T_G-open. Also ?F(F?^(-1) (A,B))?(A,B). Hence F is G_B C at z. Therefore F is G_B CM.

Example 2.4.1: LetZ={1,2,3}, X={a_1,a_2 } and Y={b_1,b_2 }. Then T_G={?,{3},{1,2},{2,3},Z} and ?={(?,?),({a_1 },{b_1 } ),({a_2 },{Y} ),(X,Y) }. Clearly T_G is G_T on Z and ? is G_B T from X to Y. Define F:Z?X?Y by F(1)=(a_1,b_1 )=F(2) and F(3)=(a_2,Y). Now F^(-1) (?,?)=?, F^(-1) ({a_1 },{b_1 })={1,2}, F^(-1) ({a_2 },{Y})={3}, and F^(-1) (X,Y)=Z. This shows that the inverse image of every G_B OS in (X,Y,?) is T_G-open in (Z,T_G ). Hence F is G_B CM.

Definition 2.4.2: Let (X,Y,?) be G_B TS. Let (A,B)? ?(X)??(Y). Then (A,B) is called

Generalized binary semi-open ?(G?_B SOS) if (A,B)?Cl_? (I_? (A,B)).

Generalized binary pre-open?(G?_B POS) if (A,B)?I_? (Cl_? (A,B)).

Generalized binary ?-open ?(G?_B ?OS) if (A,B)?I_? (Cl_? (I_? (A,B))).

Generalized binary ?-open ?(G?_B ?OS) if (A,B)?Cl_? (I_? (Cl_? (A,B))).

Generalized binary regular open?(G?_B ROS) if (A,B)=I_? (Cl_? (A,B)).

Definition 2.4.2: Let (Z,T_G ) be G_T S and (X,Y,?) be G_B TS. Then the mapping F:Z?X?Y is called generalized binary semi-continuous (G_B SCM) if F^(-1) (A,B) is T_G-semi-open in (Z,T_G ) for every G_B OS (A, B) in (X,Y,?).

Example 2.4.2: Let Z={1,2,3}, X={a_1,a_2 } and Y={b_1,b_2 }. Then T_G={?,{1},{1,2},{2,3},Z} and?={(?,?),({a_1 },{b_1 } ),({a_1 },{Y} ),({a_2 },{Y} ),(X,Y) }. Clearly T_G is G_T on Z and ? is G_B T from X to Y. Define F:Z?X?Y by F(1)=(a_1,b_1 ),F(2)=(a_2,b_2 )=F(3). Now F^(-1) (?,?)=?, F^(-1) ({a_1 },{b_1 })={1}, F^(-1) ({a_1 },{Y})={1}, F^(-1) ({a_2 },{Y})={2,3} and F^(-1) (X,Y)=Z. This shows that the inverse image of every G_B OS in (X,Y,?) is T_G-semi-open in (Z,?_g ). Hence F is G_B SCM.

### Proposition 2.4.2: G_B CM ?? G_B SCM

Proof: Let (A,B) be G_B OS in (X,Y,?). Since F is G_B CM, we have F^(-1) (A,B) is T_G-open in (Z,T_G ). We know that every T_G-open set in G_T S is T_G-semi-open. Hence F^(-1) (A,B) is T_G-semi-open in (Z,T_G ). Thus F is G_B SCM.

Remark 2.4.1: The converse of Proposition 2.4.2 is illustrated in Example 2.4.3

Example 2.4.3: Let Z={1,2,3,4}, X={a_1,a_2 } and Y={b_1,b_2 }. Then T_G={?,{3},{3,4},{1,2,4},Z} and ?={(?,?),({a_1 },{b_1 } ),({a_1 },{Y} ),({a_2 },{Y} ),(X,Y)}. Clearly T_G is G_T on Z and ? is G_B T from X to Y. Define F:Z?X?Y by F(1)=(a_1,b_1 ),F(2)=F(3)=F(4)=(a_2,b_2 ). Now F^(-1) (?,?)=?, F^(-1) ({a_1 },{b_1 })={1}, F^(-1) ({a_1 },{Y})={1}, F^(-1) ({a_2 },{Y})={2,3,4} and F^(-1) (X,Y)=Z. This shows that the inverse image of every G_B OS in (X,Y,?) is T_G-semi-open in (Z,T_G ). Hence F is G_B SCM but not G_B CM because {2,3,4} is T_G-semi-open but not T_G-open in (Z,T_G ).

### Proposition 2.4.3: G_B CM ?? G_B ?CM

Proof: Let (A,B) be G_B OS in (X,Y,?). Since F is G_B CM, we have F^(-1) (A,B) is T_G-open in (Z,T_G ). We know that every T_G-open set in G_T S is T_G-?-open. Hence F^(-1) (A,B) is T_G-?-open in (Z,T_G ). Thus F is G_B ?CM.

Remark 2.4.2: The converse of the Proposition 2.4.3 is illustrated in Example 2.4.4.

Example 2.4.4: Let Z={1,2,3,4}, X={a_1,a_2 } and Y={b_1,b_2 }. Then T_G={?,{1,2} {2,3,4},Z} and ?={(?,?),({a_1 },{b_1 } ),({a_1 },{b_2 } ),({a_1 },{Y} ),(X,Y) }. Clearly T_G is G_T on Z and ? is G_B T from X to Y. Define F:Z?X?Y by F(1)=(a_1,b_1 )= F(2)=F(3). Now F^(-1) (?,?)=?, F^(-1) ({a_1 },{b_1 })={1,2,3} , F^(-1) ({a_1 },{b_2 })={?}, F^(-1) ({a_1 },{Y})={1,2,3} and F^(-1) (X,Y)=Z. This shows that the inverse image of every G_B OS in (X,Y,?) is T_G-?-open in (Z,T_G ). Hence F is G_B ?CM but not G_B CM because {1,2,3} is T_G-?-open but not T_G-open in (Z,T_G ).

## G_B RCM ?? G_B CM

Proof: Let (A,B) be G_B OS in (X,Y,?). Since F is G_B ?CM, we have F^(-1) (A,B) is T_G-?-open in (Z,T_G ). We know that every T_G-?-open set in G_T S is T_G-semi-open (T_G-pre-open). Hence F^(-1) (A,B) is T_G-semi-open (T_G-pre-open) in (Z,T_G ). Thus F is G_B SCM (G_B PCM).

Similarly let (A,B) be G_B OS in (X,Y,?).. Suppose F is G_B RCM , we have F^(-1) (A,B) is T_G-r-open in (Z,T_G ). We know that every T_G-r-open set is T_G-open. Hence F^(-1) (A,B) is T_G-open in (Z,T_G ). Thus F is G_B CM, which proves (iii).

Remark 2.4.3: The converse of the Proposition 2.4.4 is illustrated in Example 2.4.5, Example 2.4.6 and Example 2.4.7.

Example 2.4.5: Let Z={1,2,3,4}, X={a_1,a_2 }, Y={b_1,b_2 }. Then T_G={?,{2},{2,3},{3,4},{2,3,4},Z} and ?={(?,?),({a_1 },{b_1 } ),({a_1 },{Y} ),({a_2 },{Y} ),(X,Y) }. Clearly T_G is G_Ton Z and ? is G_B T from X to Y. Define F:Z?X?Y by F(1)=F(2)=(a_1,b_1 ), F(3)=F(4)=(b_1,b_2 ). NowF^(-1) (?,?)=?, F^(-1) ({a_1 },{b_1 })={1,2}, F^(-1) ({a_1 },{Y})={1,2}, F^(-1) ({a_2 },{Y})={3,4} and F^(-1) (X,Y)=Z. This shows that the inverse image of every G_B OS in (X,Y,?) is T_G-semi-open in (Z,T_G ). Hence F is G_B SCM but not G_B ?CM because {1,2} is T_G-semi-open but not T_G-?-open in (Z,T_G ).

Example 2.4.6: Let Z={1,2,3,4}, X={a_1,a_2 }, Y={b_1,b_2 }. Then T_G={?,{1,2},{2,3},{3,4},{1,2,3},{2,3,4},Z} and?={(?,?),({a_1 },{b_1 } ),({a_1 },{Y} ),({a_2 },{Y} ),(X,Y) }. Clearly T_G is G_T on Z and ? is G_B T from X to Y. Define F:Z?X?Y by F(1)=F(3)=F(4)=(a_1,b_1 ),F(2)=(b_1,b_2 ). Now F^(-1) (?,?)=?, F^(-1) ({a_1 },{b_1 })={1,3,4}, F^(-1) ({a_1 },{Y})={1,3,4}, F^(-1) ({a_2 },{Y})={?} and F^(-1) (X,Y)=Z. This shows that the inverse image of every G_B OS in (X,Y,?) is T_G-pre-open in (Z,T_G ). Hence F is G_B PCM but not G_B ?CM because {1,3,4} is T_G-pre-open but not T_G-?-open in (Z,T_G ).

Example 2.4.7: Let Z={1,2,3,4}, X={a_1,a_2 }, Y={b_1,b_2 }. Then T_G={?,{2},{2,3},{3,4},{2,3,4},Z} and ?={(?,?),({a_1 },{b_1 } ),({a_1 },{Y} ),({a_2 },{Y} ),(X,Y) }. Clearly T_G is G_T on Z and ? is G_B T from X to Y. Define F:Z?X?Y by F(2)=F(3)=(a_1,b_1 ),F(1)=f(4)=(b_1,b_2 ). Now F^(-1) (?,?)=?, F^(-1) ({a_1 },{b_1 })={2,3}, F^(-1) ({a_1 },{Y})={2,3}, F^(-1) ({a_2 },{Y})={?} and F^(-1) (X,Y)=Z. This shows that the inverse image of every G_B OS in (X,Y,?) is T_G-open in (Z,T_G ). Hence F is G_B CM but not G_B RCM because {2,3} is T_G-open but not T_G-regular open in (Z,T_G ).

### Remark 2.4.4: G_B SCM ? G_B PCM

This can be illustrated in Example 2.4.8 and Example 2.4.9.

Example 2.4.8: Let Z={1,2,3,4}, X={a_1,a_2 } and Y={b_1,b_2 }. Then T_G={?,{1},{2} {1,2},{1,3},{2,3},{1,2,3},Z}and?={(?,?),({a_1 },{b_1 } ),({a_1 },{Y} ),({a_2 },{Y} ),(X,Y) }. Clearly T_G is G_T on Z and ? is G_B T from X to Y. Define F:Z?X?Y by F(2)=F(3)=F(4)=(a_2,b_2 ). Now F^(-1) (?,?)=?, F^(-1) ({a_1 },{b_1 })={?}, F^(-1) ({a_1 },{Y})={?}, F^(-1) ({a_2 },{Y})={2,3,4} and F^(-1) (X,Y)=Z. This shows that the inverse image of every G_B OS in (X,Y,?) is T_G-semi-open in (Z,T_G ). Hence F is G_B SCM but is not G_B PCM, because {2,3,4} is not T_G-pre-open in (Z,T_G ).

Example 2.4.9: Let Z={1,2,3}, X={a_1,a_2 } and Y={b_1,b_2 }. Then T_G={?,{1,2},{2,3},Z} and ?={(?,?),({a_1 },{b_1 } ),({a_1 },{Y} ),({a_2 },{Y} ),(X,Y) }. Clearly T_G is G_T on Z and ? is G_B T from X to Y. Define F:Z?X?Y by F(1)=(a_1,b_1 )=F(3),F(2)=(?,b_2 ). Now F^(-1) (?,?)=?, F^(-1) ({a_1 },{b_1 })={1,3}, F^(-1) ({a_1 },{Y})={1,3}, F^(-1) ({a_2 },{Y})={?} and F^(-1) (X,Y)=Z. This shows that the inverse image of every G_B OS in (X,Y,?) is T_G-pre-open in (Z,T_G ). Hence F is G_B PCM but is not G_B SCM because {1,3} is not T_G-semi-open in (Z,T_G ).